2012
DOI: 10.1074/jbc.m112.385674
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Protein for Xenopus Kinesin-like Protein 2 (TPX2) Regulates γ-Histone 2AX (γ-H2AX) Levels upon Ionizing Radiation

Abstract: Background: TPX2 is as an essential protein for mitosis, but its nuclear function is unknown. Results: TPX2 goes to DNA double strand breaks and regulates ␥-H2AX levels upon ionizing radiation. Conclusion:We discover a novel and the first nuclear function for TPX2. Significance: Our study provides new insights into the physiological and oncological roles of TPX2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 85 publications
(87 reference statements)
3
51
0
Order By: Relevance
“…79,80 Upon ionizing radiation, TPX2 accumulates at DNA double strand breaks and associates with 2 regulators of the DNA damage response, MDC1 and ATM. 81 Overexpression of TPX2 results in decreased ionizing radiation-dependent γ-H2AX levels, whereas the opposite phenotype is observed upon TPX2 knockdown by RNA interference. This function is not associated with the mitotic roles of TPX2, since it is also observed in postmitotic neurons.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…79,80 Upon ionizing radiation, TPX2 accumulates at DNA double strand breaks and associates with 2 regulators of the DNA damage response, MDC1 and ATM. 81 Overexpression of TPX2 results in decreased ionizing radiation-dependent γ-H2AX levels, whereas the opposite phenotype is observed upon TPX2 knockdown by RNA interference. This function is not associated with the mitotic roles of TPX2, since it is also observed in postmitotic neurons.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This function is not associated with the mitotic roles of TPX2, since it is also observed in postmitotic neurons. 81 Whether Aurora-A is involved in this phenotype remains unknown. These data suggest that deregulation of TPX2 may be involved not only in chromosomal instability but also in genomic instability mediated by abnormal DNA damage response (Fig.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…TPX2 has been recently reported to promote interkinetic nuclear migration in mouse neural cells, by re-organising apical microtubules during the G2 phase (Kosodo et al, 2011). DNA damage response (DDR): recent data show that TPX2 is involved in DDR to ionising radiations, by modulating the levels of γ-H2AX; TPX2 localises to DNA double strand breaks and interacts with DDR factors such as MDC1 (Neumayer et al, 2012). Previous data suggested a link between TPX2 and DDR: i) TPX2 is a putative substrate of the ATM/ATR kinases, as revealed in a large-scale proteomic screening (Matsuoka et al, 2007); ii) a functional interplay has been shown between Xenopus TPX2, the Aurora-A kinase and the p53 oncosuppressor (Pascreau et al, 2009).…”
Section: Functionmentioning
confidence: 99%
“…It has been found to be a nuclear proliferation-related protein which is implicated in the regulation of the cell mitosis. TPX2 is released in the early stage of mitosis; and plays a critical role in mitotic spindle formation and subsequent segregation of chromosomes at cell division [14] . In recent years, a connection between TPX2 and initiation, progression and prognosis of malignant tumor is becoming a focus of researches [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant expression of TPX2 leads to improper spindle assembly and chromosomal instability; and these processes might be partly responsible for carcinogenesis [14] . However, the precise role of TPX2 in cancer progression is still not fully understood.…”
mentioning
confidence: 99%